EVALUATION OF PASSENGER RATES ON FERRY SHIP ON BATULICIN-TANJUNG SERDANG LINE, TANAH BUMBU REGENCY, SOUTH KALIMANTAN PROVINCE - Sutrisno, Slamet Prasetyo; Surnata, Surnata; Rahman, Siddiq Nur (IWTJ : International Water Transport Journal, 2023)
Boom Baru Port Palembang serves loading and unloading services. In the implementation of loading and unloading activities, it is highly dependent on the availability of stevedoring workers. Based on a field survey, it was found that in loading and unloading activities, several handling of loading and unloading activities, the number of workers used in the implementation of loading and unloading activities was not ideal, the working hours of stevedoring workers exceeded the regulatory limits and the competency certification of stevedoring workers had not been met. The purpose of this study was to determine the number of stevedoring workers in each handling of loading and unloading activities. This study used an observation method in the field by analyzing stevedoring workers, working hours, and stevedoring worker certification. Based on this analysis, it was found that the need for workers in each handling of loading and unloading was different, the working hours of stevedoring workers exceeded the specified standards and the competency certification of stevedoring workers was not sufficient. In order to improve performance in loading and unloading activities, scheduling is needed in loading and unloading activities to reduce excessive working hours and provide education and training to improve the competence of stevedoring workers.